2009
DOI: 10.1002/cphc.200900405
|View full text |Cite
|
Sign up to set email alerts
|

UV Polymerisation of Surfactants Adsorbed at the Nematic Liquid Crystal–Water Interface Produces an Optical Response

Abstract: We have investigated the changes in crossed polariser optical textures produced by adsorption and UV polymerisation of a range of polymerisable surfactants at the interface between a nematic liquid crystal and water. Similar to non-polymerisable surfactants, the adsorption of polymerisable surfactants with sufficiently long hydrophobic tail groups produces a transition from planar to homeotropic anchoring. UV polymerisation of surfactants with a polymerisable group located in the hydrophobic tail region change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 46 publications
2
33
0
Order By: Relevance
“…These studies provide support for the hypothesis that the interaction of the LC with the amphiphiles is mediated primarily via the tail of the lipid 52, 61, 64. For example, one study used two forms of dodecylbenzenesulfonate(DBS) (linear L-DBS and branched BR-DBS, shown in Figure 5E) to investigate the effects of surfactant tail structure on the ordering of the LC 52.…”
Section: Section 2: Aqueous Interfaces Of Thermotropic Liquid Crystalsmentioning
confidence: 81%
See 1 more Smart Citation
“…These studies provide support for the hypothesis that the interaction of the LC with the amphiphiles is mediated primarily via the tail of the lipid 52, 61, 64. For example, one study used two forms of dodecylbenzenesulfonate(DBS) (linear L-DBS and branched BR-DBS, shown in Figure 5E) to investigate the effects of surfactant tail structure on the ordering of the LC 52.…”
Section: Section 2: Aqueous Interfaces Of Thermotropic Liquid Crystalsmentioning
confidence: 81%
“…al . using UV-polymerizable surfactants showed that polymerization of the hydrophobic tail of a surfactant at the LC-aqueous interface changes the ordering of the LC from homeotropic to planar, whereas polymerization of the hydrophilic head region does not produce a similar LC ordering transition 61. These results combined indicate that the surfactant head group does not have a large effect on the orientation of 5CB, whereas the aliphatic tail structure, length, and conformation greatly affect the ordering of the LC.…”
Section: Section 2: Aqueous Interfaces Of Thermotropic Liquid Crystalsmentioning
confidence: 95%
“…Subsequently, Kuhnau et al used differential scanning calorimetry (DSC) to determine that LCs penetrate into dipalmitoylphosphatidylcholine (DPPC) bilayers, leading to a change in the ordering of the acyl chains of DPPC 50,51. Finally, in a recent and elegant experiment, Fletcher et al reported that UV polymerization of the tails of surfactants at aqueous-LC interfaces frustrates homeotropic ordering of the LC whereas polymerization of the headgroup does not perturb the system from the homeotropic orientation 19. All these experiments support the view that homeotropic anchoring of LCs on lipid-decorated surfaces is induced by the interdigitation (or penetration) of mesogens into the aliphatic chains of the amphiphiles.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, early work by Hiltrop and Stegemeyer demonstrated that the ordering of LCs at surfaces can be influenced by the presence of monolayers of lecithin transferred onto the surfaces by the Langmuir-Blodgett (LB) technique 15,16. More recently, the influence of surfactants and phospholipids self-assembled at aqueous-LC interfaces on the ordering of LCs has been reported 11,17-19. These past studies, when combined, suggest a physical picture in which monolayer films of phospholipids organize to present their hydrophobic tails towards the LC phase, thus leading to interdigitation of mesogens and lipid acyl chains with the subsequent homeotropic (perpendicular) ordering of the LCs.…”
Section: Introductionmentioning
confidence: 99%
“…1 For this class of adsorbates, the steric interactions of the tails of the amphiphiles and the mesogens of the thermotropic LC have been shown to couple the interfacial organization of the amphiphiles to the orientational ordering of the LC. 914 For example, contact of an aqueous dispersion of vesicles of dilauroylphosphatidylcholine (DLPC) with the interface of a micrometer-thick film of nematic 4′-pentyl-4-cyanobiphenyl (5CB) has been observed to result in spontaneous formation (via fusion) of a monolayer of DLPC on the interface of the LC, resulting in a discontinuous orientational ordering transition in which the LC changes from an orientation that is parallel to the interface (prior to lipid adsorption) to perpendicular to the interface (after lipid adsorption). 9 In addition, it was observed that, at interfacial densities of DLPC below saturation coverage, the DLPC monolayer exhibited coexisting lipid-rich and lipid-lean domains which gave rise to patterned orientations of the LC.…”
Section: Introductionmentioning
confidence: 99%